The Whistles of George Wallace: Gender and Emotions in the 1968 Presidential Campaign - Maarten Zwiers (European Journal of American Studies)
Gender and emotions are important factors in the rise of modern U.S. conservatism. This article examines the 1968 presidential election as a pivotal moment in the development of the New Right. During that campaign, George Wallace practiced a masculine political style that evoked an emotional response from anxious voters who felt alienated and angry. Wallace set the stage for a conservative political strategy that remains effective until this day.